Integrative Da’wah Strategy: A Model for Student Community Service (Kukerta) Programs - Angger Bimantara; Muhammad Rifki Rizqullah; Muhammad Wahyu Abdi Nugroho (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2026)
This study examines the absence of an integrative da’wah model within the KUKERTA student program that unifies traditional, digital, bil-hal (practical action), participatory, and contextual approaches. The aim of this research is to analyze the integrative da’wah strategies implemented by students in the KUKERTA Al-Mubarak program and to formulate an adaptive and replicable conceptual model. This study employs a qualitative field research design using observation, interviews, and documentation. Data analysis follows the Miles and Huberman model, integrated with the Da’wah Process Theory, which includes input, conversion, output, impact, and feedback in a systematic framework. The findings indicate that the integrative da’wah strategy of KUKERTA Al-Mubarak students consists of five complementary approaches implemented across five villages in Gunungkidul. The traditional approach strengthens religious literacy through study circles, Qur’anic recitation improvement (tahsin), and Qur’an learning centers (TPA). The digital approach expands da’wah outreach through podcasts and social media platforms. The bil-hal and participatory strategies enhance community engagement in social and religious activities, while the contextual approach introduces innovations based on local cultural values. The results show increased congregation participation, strengthening of local da’wah cadres, mosque revitalization, and broader dissemination of da’wah messages through digital media, contributing to sustainable socio-religious transformation. In conclusion, the integrative da’wah strategy implemented by KUKERTA students is effective, adaptive, and capable of producing sustainable socio-religious change within the community. The significance of this study lies in its contribution to the development of an integrative da’wah model, the strengthening of the implementation of community service learning (KKN/KUKERTA), and the promotion of innovation in community-based da’wah practices in rural areas.